Recognition of Prior Learning as “Radical Pedagogy”: A case study of the Workers' College in South Africa - wa Bofelo, Mphutlane; Shah, Anitha; Moodley, Kessie; Cooper, Linda; Jones, Barbara (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
This article argues that the model of Recognition of Prior Learning (RPL) in use at the Workers’ College in South Africa may be seen as a form of “radical pedagogy.” Drawing on documentary sources, focus group interviews with staff, and observations, it describes an educational philosophy which aims to build the competencies of activists in labour and community organizations, facilitate their self-affirmation and dignity, and provide an access route to post-school education. It documents and attempts to theorize how this philosophy is enacted in classroom pedagogy, and explores some of the tensions and contradictions encountered. It concludes by acknowledging the unique contribution of these educational practices to an understanding of what RPL as radical pedagogy might look like.